Analisis Sentimen Pelaksanaan Vaksinasi Covid-19 secara Massal pada Media Sosial Twitter - Adinda Febby Nuraini; Rosma Dian Pertiwi; Muhammad Zidni Subarkah; Kiki Ferawati (Seminar Nasional Official Statistics, 2022)
The corona virus or Covid-19 attacks almost all countries in the world, as well as Indonesia. The Indonesian government has implemented several policies to deal with the spread of the Covid-19 in the community, namely by mass vaccination. The implementation of mass vaccination has become trending on Twitter. This study aims to analyze the sentiment of mass vaccination in Indonesia using a comparison between Naïve Bayes, Random Forest, and Support Vector Machine (SVM) methods. The results showed that SVM classification method has F1-Score Weighted Average higher than other methods, which was 84%. In addition, it can be concluded that most of the community is pro against the implementation of mass vaccines. So, SVM method can be used by the government to classify public sentiment towards the next mass vaccination and basis for the government to maintain this mass vaccination program as an effort to prevent the spread of Covid-19.